Work in the Platform Economy: Beyond Lower Transaction Costs - Jan Drahokoupil; Agnieszka Piasna (Intereconomics, 2017)
Work on platforms is part of a wider trend towards the increasing fragmentation of work. It takes different forms, ranging from short spells of employment with the same employer to moving between different work arrangements to juggling multiple jobs at the same time. In all its forms, it signals an increasing job instability and is often fuelled by insufficient income from one job to cover the cost of living.
Keywords: 330